Transancestral GWAS of alcohol dependence reveals common genetic underpinnings with psychiatric disorders. (December 2018) - Walters, Raymond; Polimanti, Renato; Johnson, Emma; McClintick, Jeanette; Adams, Mark; Adkins, Amy; Aliev, Fazil; Bacanu, Silviu-Alin; Batzler, Anthony; Bertelsen, Sarah; Biernacka, Joanna; Bigdeli, Tim; et al.
Abstract Liability to alcohol dependence (AD) is heritable, but little is known about its complex polygenic architecture or its genetic relationship with other disorders. To discover loci associated with AD and characterize the relationship between AD and other psychiatric and behavioral outcomes, we carried out the largest genome-wide association study to date of DSM-IV-diagnosed AD. Genome-wide data on 14, 904 individuals with AD and 37, 944 controls from 28 case–control and family-based studies were meta-analyzed, stratified by genetic ancestry (European, n  = 46, 568; African, n  = 6, 280). Independent, genome-wide significant effects of differentADH1B variants were identified in European (rs1229984;P  = 9.8 × 10–13 ) and African ancestries (rs2066702;P  = 2.2 × 10–9 ). Significant genetic correlations were observed with 17 phenotypes, including schizophrenia, attention deficit–hyperactivity disorder, depression, and use of cigarettes and cannabis. The genetic underpinnings of AD only partially overlap with those for alcohol consumption, underscoring the genetic distinction between pathological and nonpathological drinking behaviors. Different functional variants inADH1B (and elsewhere) in Europeans and Africans strongly affect risk for alcohol dependence. Dependence only partly genetically correlates with consumption, with strong correlations to other psychiatric disorders.